Always Look on the "Light" Side of Life: Sustainable Carbon Aerogels. Issue 3 (13th January 2014) - White, Robin J.; Brun, Nicolas; Budarin, Vitaly L.; Clark, James H.; Titirici, Maria‐Magdalena
Abstract The production of carbon aerogels based on the conversion of inexpensive and abundant precursors using environmentally friendly processes is a highly attractive subject in materials chemistry today. This article reviews the latest developments regarding the rapidly developing field of carbonaceous aerogels prepared from biomass and biomass‐derived precursors, highlighting exciting and innovative approaches to green, sustainable nanomaterial synthesis. A review of the state‐of‐the‐art technologies will be provided with a specific focus on two complimentary synthetic approaches developed upon the principles of green chemistry. These carbonaceous aerogel synthesis strategies, namely the Starbon and carbogel approaches, can be regarded as "top‐down" and "bottom‐up" strategies, respectively. The structural properties can be easily tailored by controlling synthetic parameters such as the precursor selection and concentration, the drying technique employed and post‐synthesis temperature annealing. In addition to these parameters, the behavior of these sustainable carbon aerogel platforms in a variety of environmental and energy‐related applications will also be discussed, including water remediation and fuel cell chemistry (i.e., the oxygen reduction reaction). This Review reveals the fascinating variety of highly porous, versatile, nanostructured, and functional carbon‐based aerogels accessible through the highlighted sustainable synthetic platforms.